Exclusively membrane‐inserted state of an uncleavable Tat precursor protein suggests lateral transfer into the bilayer from the translocon. (24th June 2013) - Ren, Chao; Patel, Roshani; Robinson, Colin
<x xml:space="preserve">Abstract</x> In bacteria, the export of proteins by the twin‐arginine translocase (Tat) pathway is directed by cleavable N‐terminal signal peptides. We studied the relationship between transport and maturation using a substrate, YedY, that contains an Ala > Leu substitution at the ‐1 position of the signal peptide. This blocks maturation and leads to the accumulation of a membrane‐bound precursor form with the mature domain exposed to the periplasm. Its accumulation does not block transport of other Tat substrates, indicating that exit from the translocation channel has taken place, and the precursor protein is fir mLy integrated into the membrane bilayer. The membrane‐integrated nature of the precursor, and complete absence of precursor protein in the periplasm, strongly suggest that the precursor has undergone lateral transfer into the bilayer during translocation. We propose that subsequent proteolytic processing releases the mature protein into the periplasm. A delay in processing results in an inhibition of cell growth, emphasizing a requirement for efficient maturation of Tat substrates.